Patient after radiofrequency ablation due to atrial fibrillation – how to approach and follow up? - Lodziński, Piotr; Koźluk, Edward (Przewodnik Lekarza/Guide for GPs, 2007)
Atrial fibrillation is the most common arrhythmia, and is the cause of 1/3 of all hospital admissions due to cardiac rhythm disturbances. Epidemiological data and an increased number of performed radiofrequency ablations in atrial fibrillation patients creates the situation that independently of medical specialty every physician may deal with the problem of post-procedure management of such a patient. The cornerstones of every decision about qualification for ablation and follow-up of patients after ablation are the ACC/AHA/ESC guidelines for the management of atrial fibrillation patients and HRS/EHRA/ECAS expert consensus on catheter and surgical ablation of atrial fibrillation which were published recently.